(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2019)
Introduction: Adequate nutrition during infancy and early childhood is fundamental to the development of child’s full human potentials. Malnutrition is recognized as one of the major causes of morbidity and mortality among the children under- five years and developing countries are the worst affected. Objectives: To assess the nutritional status of under-five children of selected area of Chattogram hill tracts of Bangladesh. Material and Methods: This cross-sectional study was conducted among 300 children with age between 6 months to 5 years, reported to the outpatients department of selected hospitals were included purposively. All the data were collected by interviewing the mothers of the children by using a pretested semi-structured questionnaire. Nutritional status was assessed by using WHO recommended height for age Z-score (HAZ) for stunting, weight for age Z-score (WAZ) for underweight, height for weight Z-score (HWZ) for wasting and mid upper am circumference (MUAC) for overall nutritional status. Results: Out of 300 children 53.3% were boys and 48.4% were aged less than 2 years. About 50.7% children were tribal and 49.3% were bengali. Majority (56.45%) of the children’s mothers’ age was below 25 years, 36.7% was illiterate, 92.7% were housewives and 85.6% had monthly family income less than 10,000 taka. Regarding children nutritional status 15.6% was moderate stunted, 30.7% was mild stunted; severe, moderate and mild underweight was 4.3%, 13.3% and 24.7% respectively. About 1.7% was found severe wasted and 15.3% was moderate wasted. By MUAC 20.3% were of moderate acute malnutrition and 3.3% were of severe acute malnutrition. Conclusion: This study result revealed a high prevalence of malnutrition among under-five children in the study area. Considering the acute and long-term consequences of malnutrition special interventions program is needed to overcome the situation. Journal of Armed Forces Medical College Bangladesh Vol.14(1) 2018: 21-23